2018
DOI: 10.1111/puar.12956
|View full text |Cite
|
Sign up to set email alerts
|

Do White Law Enforcement Officers Target Minority Suspects?

Abstract: The debate over possible bias in the use of deadly force has recently been exacerbated by highly publicized killings of African American males around the country. While much research has been conducted examining police behavior, little has been done to investigate the impact of race on police behavior. This article aims to answer this question: are white police officers more likely to use lethal force on minority suspects or people of a specific race? To answer this question, the authors construct a data set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…However, averaging across shootings may provide an incomplete picture if racial disparities vary across types of fatal shootings. The remaining models (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) separate different types of shootings to test for this variation. No model showed significant evidence of anti-Black or -Hispanic disparity, although evidence for anti-Black and anti-Hispanic disparities was stronger when civilians were young (Model 1 vs. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, averaging across shootings may provide an incomplete picture if racial disparities vary across types of fatal shootings. The remaining models (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) separate different types of shootings to test for this variation. No model showed significant evidence of anti-Black or -Hispanic disparity, although evidence for anti-Black and anti-Hispanic disparities was stronger when civilians were young (Model 1 vs. 2).…”
Section: Resultsmentioning
confidence: 99%
“…data. The only national examination of this question found that White officers were no more likely to fatally shoot Black or Hispanic civilians than non-White officers (13). However, their key analyses were based on only a small subset (19-23%) of all fatal shootings.…”
mentioning
confidence: 99%
“…Recent studies in public administration have emphasized the impact of institutions on racial disparities in policing outcomes, as opposed to individual‐level behaviors (Epp, Maynard‐Moody, and Haider‐Markel ; Eterno, Barrow, and Silverman ; Hong ; Jennings and Rubado ; Kim and Kiesel ; Maynard‐Moody and Musheno ; Menifield, Shin, and Strother ; Rivera and Ward ). While these studies effectively demonstrate the relevance and importance of widely prevalent norms, rules, and values in driving racially disparate criminal justice outcomes, the role of accountability institutions has not received sufficient attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the Federal Bureau of Investigation does collect data on police-involved civilian deaths, these data are subject to substantial underreporting, the extent of which varies across jurisdictions (Barber et al 2016). Several recent public administration studies studying PHCs have either directly used the FE database or used it to cross-check data gathered from other crowdsourced databases (see Jennings and Rubado 2017;Menifield, Shin, and Strother 2019;Nicholson-Crotty, Nicholson-Crotty, and Fernandez 2017).…”
Section: Figure 3 Geographic Dispersion Of Coas In the Contiguous Unimentioning
confidence: 99%
“…Continuing the theme, Menifield, Shin, and Strother () find that an officer's race plays no role in influencing the use of lethal force against minority suspects. Amirkhanyan et al () find that managers prioritize diversity efforts when facing higher levels of regulatory violations, and that the effect of managerial strategies for diversity on performance is conditioned by the racial composition of the clients.…”
Section: New Developments In Social Equity As a Public Valuementioning
confidence: 99%